Comparison of esthetic outcome after extraction or non-extraction orthodontic treatment in class II division 1 malocclusion patients - Sneh Lata Verma; V P Sharma; Pradeep Tandon; Gyan P Singh; Kiran Sachan (Wolters Kluwer Medknow Publications, 2013)
Introduction: The extraction of premolars as a practical form of orthodontic therapy has been accepted for many years, but there remains a controversy regarding the effect of premolar extraction to improve esthetics as well as dentoskeletal relationship. The esthetic impact of the soft-tissue profile might play a major role in deciding on premolar extraction or non-extraction treatment, particularly in borderline patients. This cephalometric study was undertaken to compare the post-treatment soft-tissue profiles of successfully managed Class II, Division 1 malocclusions treated with either all first premolar extractions or treatment with a non-extraction therapy. Materials and Methods: The sample consisted of 100 post-pubertal female patients of Class II Division I malocclusion. Group 1, treated with four first premolar extractions, consisted of 50 female patients with a mean age of 14 years 1 month. Group 2, treated without extractions, consisted of 50 patients with a mean age of 13 years 5 months. Pre-treatment and post-treatment lateral cephalometric radiographs were evaluated. The pre-treatment to post-treatment stage comparison and the intergroup comparison of the treatment changes were conducted between extraction and non-extraction groups of Class II malocclusion samples with t-tests. Results: The soft-tissue facial profiles of the extraction and non-extraction samples were the same following active treatment except for a more retruded lower lip and a more pronounced lower labial sulcus in those patients subjected to extraction. Conclusions: The extraction or non-extraction decision, if based on sound diagnostic criteria, seems to have no systematic detrimental effects on the facial profile.